2016
DOI: 10.1055/s-0036-1593409
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and Metabolic Syndrome Biomarker Analysis of Vascular Outcomes in End-stage Renal Disease

Abstract: End-stage renal disease (ESRD) presents a complex syndrome in which inflammatory and metabolic processes contribute to disease progression and development of comorbid conditions. Over $1 trillion is spent globally on ESRD care. Plasma samples collected from 83 ESRD patients prior to hemodialysis were profiled for metabolic and inflammatory biomarker concentrations. Concentrations were compared between groups with and without history of stroke, acute coronary syndrome (ACS), congestive heart failure (CHF), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Qin et al described that decreased leptin levels were an independent risk factor for LVH development in patients on hemodialysis [ 112 ]. Curiously, in ESRD, patients with a history of stroke presented higher leptin levels than those without stroke history, while patients with congestive heart failure showed lower leptin values that those without history of congestive heart failure [ 113 ].…”
Section: Leptinmentioning
confidence: 99%
“…Qin et al described that decreased leptin levels were an independent risk factor for LVH development in patients on hemodialysis [ 112 ]. Curiously, in ESRD, patients with a history of stroke presented higher leptin levels than those without stroke history, while patients with congestive heart failure showed lower leptin values that those without history of congestive heart failure [ 113 ].…”
Section: Leptinmentioning
confidence: 99%
“… 16 , 17 Furthermore, this elevation has also shown to be associated with the progression of CKD to ESRD with higher rates of cardiovascular complications and mortality in this patient group. 17 20 Interestingly, major improvements were observed at the levels of inflammatory biomarkers after kidney transplantation; this has indicated that inflammation is not only a cause but also a consequence in the development of a kidney disease and its associated complications. 21 Regarding this, several dialysis-related factors have been associated with persistent and low-grade inflammation in ESRD.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased leptin levels were also associated with a higher risk of CV events in hemodialysis patients and was also considered an independent risk factor for LVH development [ 19 ]. Interestingly, in ESKD, while patients with a history of stroke presented higher leptin levels than those without a stroke history, patients with congestive heart failure showed lower leptin than those without a history of congestive heart failure [ 20 ]. Given the controversial data, further studies are warranted to fully clarify leptin’s role, namely, its association with morbidity and mortality risks and its contribution to LVH development in CKD and, especially, in ESKD.…”
Section: Introductionmentioning
confidence: 99%